Effect of Dexmedetomidine on Postoperative Sleep Quality: A Systematic Review - Huang X; Lin D; Sun Y; Wu A; Wei C (Dove Medical Press, 2021)
Xiao Huang,* Dandan Lin,* Yi Sun, Anshi Wu, Changwei Wei Department of Anesthesiology, Beijing Chao-Yang Hospital, Capital Medical University, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Changwei WeiDepartment of Anesthesiology, Beijing Chao-Yang Hospital, Capital Medical University, No. 8, South Workers Stadium Road, Chaoyang District, Beijing, People’s Republic of ChinaTel +86 10-85231330Email changwei.wei@ccmu.edu.cnAbstract: In this article, we conduct a systematic review of the literature to explore the specific role of dexmedetomidine (DEX) on postoperative sleep and its associated mechanisms at present. The electronic database Embase, MEDLINE/PubMed, the Cochrane Library, Web of Science, and Google Scholar were searched. The restriction terms included “dexmedetomidine”, “sleep” and “surgery”. The inclusion criteria were as following: 1) patients 18 years old or older; 2) DEX used in the perioperative period not just for critically ill patients in the intensive care unit (ICU); 3) prospective or retrospective studies. The review articles, conference abstracts, and animal studies were excluded. Out of the 22 articles which met the above criteria, 20 of them were randomized controlled studies and 2 of them were retrospective cohort studies. Infusion of DEX including during the surgery and after surgery at a low or high dose was shown to improve subjective and objective sleep quality, although 2 studies showed there is no evidence that the use of DEX improves sleep quality and 1 showed less sleep efficiency and shorter total sleep time in the DEX group. Other postoperative outcomes evaluated postoperative nausea and vomiting, pain, postoperative delirium bradycardia and hypotension. Outcomes of our systematic review showed that DEX has advantages in improving patients’ postoperative sleep quality. Combined with the use of general anesthetic, DEX provides a reliable choice for procedural sedation.Keywords: dexmedetomidine, sleep, surgery